From Reform to Results: Competency-Based Talent Management in Malaysian Public Universities - Mohamad Nasaruddin Mahdzir; Muhamad Tasyrif Ghazali (Indonesian Educational Research Journal, 2025)
Malaysian public universities occupy a strategic role in advancing national development, yet they face persistent challenges linked to graduate employability, financial sustainability, and talent management. The introduction of the Public Service Remuneration System (SSPA) signaled a paradigm shift in the public sector by promoting meritocracy, performance-based rewards, and competency development through instruments such as MyPerformance, MyKompetensi, and MyPotensi. However, empirical evidence indicates a misalignment between macro-level policy intentions and the operational realities of universities, where performance indicators remain overly academic and training programs generic. This study adopts a qualitative design that integrates documentary analysis and researcher observation within a Malaysian public university to explore how SSPA principles can be effectively contextualized through competency-based talent management instruments. The findings reveal persistent gaps in linking remuneration, competency, and institutional outcomes. To address these gaps, a conceptual framework is proposed that integrates SSPA with four contextualized instruments: Competency-Based Talent Management (CBTM), Behavioral Event Self-Assessment (BESA), Competency-Based Interview (CBI), and Individual Development Plan (IDP). The framework serves as a bridge between policy aspirations and institutional practice, emphasizing data-driven competency mapping, merit-based selection, and personalized staff development. Theoretically, it contributes to leadership and talent management literature in higher education; practically, it provides actionable guidance for building transparent, performance-oriented, and resilient talent systems. Overall, the framework advances human capital reform and enhances the administrative effectiveness of Malaysian public universities in meeting global higher education challenges.